Recurrent copy number gains of ACVR1 and corresponding transcript overexpression are associated with survival in head and neck squamous cell carcinomas - Ambrosio, Eliane P. [UNESP]; Linde, Sandra Aparecida Drigo [UNESP]; Bergamo, Nadia A.; Rosa, Fabiola E.; Bertonha, Fernanda B.; de Abreu, Francine B.; Kowalski, Luis P.; Rogatto, Silvia Regina [UNESP] (Wiley-Blackwell, 2011)
Aims: This study aimed to evaluate the copy number alteration on 2q24, its association with ACVR1 transcript expression and the prognostic value of these data in head and neck squamous cell carcinomas.Methods and results: Twenty-eight samples of squamous cell carcinoma were evaluated by fluorescence in situ hybridization (FISH) using the probes RP11-546J1 (2q24) and RP11-21P18 (internal control). Significant gains at 2q24 were detected in most cases at frequencies varying from 3 to 35%. ACVR1 gains and amplifications were associated with longer overall survival (P = 0.022). ACVR1 mRNA expression analysis in 78 cases revealed overexpression in 44% (34 of 78) of these tumours, suggesting that gene copy number alterations could be involved in gene overexpression. In laryngeal carcinomas, overexpression of ACVR1 mRNA levels was associated with longer overall survival (P = 0.013). Multivariate analysis revealed that ACVR1 is an independent prognostic marker in laryngeal carcinomas (P = 0.012, hazard ratio = 0.165, 95% confidence interval = 0.041-0.668).Conclusions: These findings suggest that copy number alterations at 2q24 can be involved in ACVR1 overexpression, which is associated with longer overall survival in laryngeal carcinomas. To our knowledge, this is the first report indicating the relevance of ACVR1 expression in head and neck cancers.
Keywords: ACVR1; chromosomal abnormalities; FISH; head and neck cancer; laryngeal carcinomas; oral carcinomas; pharyngeal carcinomas; qRT-PCR